Technological tools for failure assessment in the flexible pavement surface, a systematic review - Cárdenas Resines , Claudia Luz (2023)
Throughout the years in which a pavement is in service, it is exposed to climatic actions and traffic that wear out its useful life, as well as its quality of mechanical characteristics, as well as functional, causing various failures and types of failures to exist. clothing on flexible pavements; Therefore, using technological option tools has become essential for their respective evaluations. Aim. Perform an analysis of existing failure assessment technology tools in flexible pavement surfaces. Type of research. The research presents a qualitative approach, which is supported by obtaining reference information on technological tools for evaluating failures in flexible pavements. Method. It was carried out through bibliographic reviews of scientific articles; Therefore, for this study, the use of databases such as: REDALYC, SCIENCEDIRECT, DIALNET, SCIELO; whose applied criteria were in terms of temporality the last 16 years (2007 - 2023), working with a total of 31 original scientific articles, to later carry out the collection of information and finally the analyzes related to our objectives. Conclusion. Terrestrial photogrammetry and neural networks is the best technological option for the evaluation of failures in the surface condition of flexible pavements; since it contributes to the reduction of time and cost, being the most efficient of the other technological tools.